Avaliação dos impactos ambientais do cemitério municipal Santa Isabel, Tucuruí-PA - CAMPOS, Andressa Larissa do Nascimento (2024)
Cemeteries are considered potential sources of pollution if built without planning, as the process of burying corpses can result in contamination of soil and surface and underground water. Therefore, these are potential sources of physical, chemical and biological contamination, which poses serious risks to urban spaces and adjacent areas. In this sense, the present research aimed to identify the possible environmental impacts generated in a public cemetery in the municipality of Tucuruí – PA. To this end, procedures such as historical analysis of the expansion of the study area were carried out; technical and legal analysis of the area in light of current legal instruments to identify the cemetery’s compliance with the requirements established by Conama Resolution n◦ 402/2008; the characterization of socio-environmental impacts assessed using the RIAM matrix; In addition to this, with the aim of proposing mitigating/corrective measures, the GUT matrix was applied, in order to establish an order of priorities for the strategic direction of the impacts revealed by the matrix. As results, the historical analysis of the study area indicated that in the period from 2005 to the present day, 605 people were buried, the cemetery is active, with a reduced number of burials, with family members of people buried there also being buried there. it was found that the cemetery does not meet any of the requirements required by current legislation, such as the lack of presentation of the documents required in the Preliminary and Installation License phase for the environmental licensing of the project, as well as the cemetery does not comply with the requirements assigned for horizontal necropolises, as well as solid waste resulting from the exhumation of bodies do not have adequate environmental and sanitary disposal, whereas the RIAM methodology pointed out a predominance of negative impacts for all aspects evaluated: physical and chemical, ecological and biological, social and cultural, economic and operational. The classification of the GUT matrix indicated that the impacts that stand out most in the cemetery point to underground water contamination, changes in sanitary conditions, proliferation of synanthropic fauna, compromising the health of workers and users of the cemetery. Therefore, it is concluded based on the data and results presented that the precariousness present in the Santa Isabel cemetery makes this enterprise susceptible to contamination by necrochorume, configuring a problem that requires strategies to be considered and discussed by the municipal authorities with the aim of promoting adequacy of the cemetery to current legal instruments and technical-management measures, so that it provides quality of life and environmental health to the surrounding communities.